Effect of Pretreatment on Seed Germination of Pinus roxburghii, Sarg. in Uttaranchal Himalaya, India - Pandit, Atul; Ram, Jeet (Indian Forester, 2006)
Pinus roxburghii (Chir pine) is a major forest forming species in the hills between 450- 2300m altitude. It has a great promise in afforestation programme in degraded and barren areas because it has the ability to grow eyen in the harsh environmental conditions. In the present study, 11 pretreatment were given to seeds to see the effect on germination. The two-way ANOVA between the sites and pretreatment was not significant. which indicates that Pinus roxburghii has almost similar germination in all the treatments. The mean germination varies from 83.00% to 95.75% for all the treatments. The mean germination was slightly higher for Soni and Matiyal forests for almost all the treatments. which may be considered a seed source for the future seed collection and afforestation programme.